Setting our research agendas: Institutional ecology, informing sciences, or management fashion theory? - Myers, M.; Baskerville, Richard; Gill, G.; Ramiller, N. (Association for Information Systems, 2011)
A new reflexive discourse is emerging in the IS research community concerning how we, as academic scholars in the Information Systems field, set and pursue our research agendas. How should we choose our research topics, how should we conduct our research, and how should we communicate our research results? This article is based on a panel discussion at the 2010 International Conference on Information Systems (ICIS) held in Saint Louis, Missouri, USA. Three distinct perspectives concerning the setting of our research agendas in Information Systems were presented and debated.